West Sumatra Basketball Coaches Capacity Improvement In Making Physical and Mental Training Programs for Athletes - Windo Wiria Dinata; Gumi Langerya Rizal; Mario Pratama (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
At present, the achievements of basketball in West Sumatra have not shown a significant increase. PERBASI West Sumatra has made various efforts through programs that have been made for basketball achievements in West Sumatra. To overcome this problem, it is necessary to add a program that also pays attention to the coach's side, where the coach is the person who is considered to have the most important role in improving the athlete's ability. This community service activity involved basketball coaches in West Sumatra in general and Pariaman City in particular. This trainer capacity building activity begins on 20-21 August 2022, at 09.00-12.00 WIB and takes place on the second floor of the LKAAM Building, Pariaman City, Pauh Barat Village, Central Pariaman District. Submission The physical exercise material presented recommends following the principles of Frequency, Intensity, Time, and Type. As for mental training, it is recommended to apply methods such as imagery and visualization as well as relaxation. The activity was attended by 25 participants. On the first day, the material for physical training was discussed, while the second day for mental training was the subject of discussion. Based on the results of the evaluation, it can be concluded that the participation of the basketball coaches and sports teachers who took part in this activity was quite good and the coaches and sports teachers also looked enthusiastic and enthusiastic.